Efektivitas Media Journey Board Game Terhadap Kemampuan Berfikir Kritis Siswa Pada Pendidikan Pancasila Kelas IV Sekolah Dasar - Fahmi Maria Ulfa; Hamidaturrohmah Hamidaturrohmah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the effectiveness of the Journey Board Game media on fourth-grade students’ critical thinking skills in Pancasila Education. The research employed a quantitative approach with a quasi-experimental nonequivalent control group pretest-posttest design. The sample consisted of 69. Students were divided into experimental and control groups. Data was collected through multiple-choice tests based on indicators of critical thinking. In addition, observations were conducted to examine students’ engagement during the learning process. The data were analyzed using independent sample t-tests for normality, homogeneity. The findings revealed that the data were distributed normally and homogeneous with a significance value of 0.578 > 0.05. Hypothesis testing revealed a significant difference between the two groups with a Sig. (2-tailed) value of 0.006 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the Journey Board Game media is effective in improving students’ critical thinking skills, strengthening conceptual understanding, and fostering a more active, interactive, engaging, and student-centered learning environment. This media also providesmeaningful learning experiences and encourages students to be actively involved in the learning process